In vitro evidence for estrogen receptor activity of selected phase II isoflavone metabolites - Dino Grgic; Dimitra Bella-Velidou; Luca Dellafiora; Sebastian T. Soukup; Sabine E. Kulling; Elisabeth Varga; Doris Marko (Archives of Toxicology, 2026)
The health benefits of soy and soy derived foods are often attributed to their isoflavone (ISFs) content, known to include phytoestrogens. However, EFSA has concluded that there is insufficient scientific evidence to establish a causal relationship between ISFs consumption and the proposed health claims. Although phase-II metabolites of ISFs are often considered as detoxified products with reduced estrogenic effects, recent studies indicate that ISFs metabolites may contribute and even enhance the biological activity of ISFs. However, current knowledge on phase-II metabolites of ISFs is limited, even though representing the major ISFs metabolites circulating in the bloodstreams in humans. This study investigates the role of phase-II metabolism in the biological activity of ISFs, focusing on estrogenicity and cytotoxicity in estrogen-sensitive Ishikawa cells (expressing estrogen receptors (ER) α and β). ISFs concentrations from 0.001 to 10 µM, with 1:10 dilution steps, were tested. Cleavage to parent compounds during incubation was also evaluated using high-performance liquid chromatography tandem mass spectrometry. The results showed that phase-II metabolites, particularly sulfates, can still exhibit estrogenic activity, challenging the general assumption that phase-II metabolism always leads to the inactivation of ISFs. In particular, at 10 µM daidzein-4'-sulfate exhibited a comparable estrogenic activity to daidzein at the same concentration, and genistein-7-sulfate exhibited estrogenic potential at higher concentrations. Molecular dynamics simulations revealed that genistein and its conjugates can stably interact with ERβ. This study highlights the importance of phase-II metabolism for ISFs activity and suggests that the sulfates formed should be examined more closely in further investigations.